2004
DOI: 10.1103/physreve.69.040901
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse scattering provides material parameters and electron density profiles of biomembranes

Abstract: Fully hydrated stacks of DOPC lipid bilayer membranes generate large diffuse x-ray scattering that corrupts the Bragg peak intensities that are used in conventional biophysical structural analysis, but the diffuse scattering actually contains more information. Using an efficient algorithm for fitting extensive regions of diffuse data to classical smectic liquid crystalline theory we first obtain the compressional modulus B= 10(13) erg/ cm(4), which involves interactions between membranes, and the bending modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
203
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(242 citation statements)
references
References 27 publications
36
203
3
Order By: Relevance
“…The electron density profile of these membranes is also in agreement with experimental profiles (see supplementary material). 62 In our coordinate system, x and y axes are in the membrane plane and z is the plane normal. DOPC and peptide molecular interactions were represented by the CHARMM v.36 force field 63,64 and water was described by the TIP3P model.…”
Section: Computationalmentioning
confidence: 99%
“…The electron density profile of these membranes is also in agreement with experimental profiles (see supplementary material). 62 In our coordinate system, x and y axes are in the membrane plane and z is the plane normal. DOPC and peptide molecular interactions were represented by the CHARMM v.36 force field 63,64 and water was described by the TIP3P model.…”
Section: Computationalmentioning
confidence: 99%
“…The radial electron density profile of the inner MT wall and outer tubulin monolayer are based on the fit to the MT scattering data. ** The parameters for the electron density profile of the lipid bilayer are based on literature data (3,30). Finally, the third tubulin layer is multiplied by the fraction, f, of tubulin coverage relative to the inner MT wall.…”
Section: Resultsmentioning
confidence: 99%
“…A chain packing statistical model of membranes (28) and experiments (29) show that k ϰ ␦ P , where ␦ is the membrane thickness. P Ϸ 3 in the case of fluid membrane, the C 12:0 and C 18:1 tails, for which ␦ Ϸ 1.2 and 1.4 nm, respectively (30). Membranes with ordered chains, the C 14:0 , C 16:0, and C 18:0 tails, for which ␦ Ϸ 1.5, 1.8, and 2 nm, respectively, are significantly more rigid, and the scaling of with ␦ is expected to be with a larger P (31, 32).…”
Section: Methodsmentioning
confidence: 99%
“…To analyze quantitatively the molecular layer stack of the Sdocosanylcysteine thin films in the present study, we have considered possible models including the Hosemann paracrystal model (Hosemann & Bagchi, 1962), the Cialle model (Liu & Nagle, 2004) and the modified Cialle model (Pabst et al, 2000), and found that the paracrystal model is the most suitable for a layer lattice in our study, as shown in Fig. 1.…”
Section: Theorymentioning
confidence: 99%